Massively enlarged styloid process presenting as a submandibular mass. (26th October 2012) - Langstaff, Lorna Elizabeth; Abed, Tarik; Philpott, Jonathan
Abstract : A 47-year-old man is investigated in the ear, nose and throat department for a 6-month history of left submandibular swelling and pain. He underwent several investigations, before a large styloid process was found on CT imaging of the neck. The patient underwent surgical excision of the enlarged styloid process and stylohyoid ligament. He recovered well with no long-term complications and his symptoms were fully resolved.